Characteristic of heat transfer nanofluid of Al2O3 improved by ZrO2 addition. Issue 1 (November 2021) - Gustaman Syarif, Dani; Usman, Jakaria; Ike Pratiwi, Yofi; Yamin, Muhammad; Hardian, Arie
Abstract: Efforts to replace conventional fluids as coolants for heat transfers with new fluids are continuously being made to improve heat transfer efficiency. Nanofluids are currently widely studied around the world as candidates for conventional fluids substitutes. In this research, the synthesis of Al2 O3 -ZrO2 nanocomposites for heat transfer nanofluid applications was carried out. The synthesis of the nanoparticles was conducted by the hydrothermal method. Here, we used ZrO2 to improve the characteristics of Al2 O3 . The results of XRD analysis showed that the nanocomposite had an Al2 O3 gamma structure. The Al2 O3 nanoparticles and Al2 O3 -ZrO2 nanocomposite have a crystallite size of 7.41 nm and 6.84 nm, respectively. The addition of 0.1 % ZrO2 decreased the crystallite size and BET particle size and increased the zeta potential, hence the stability of the nanofluids. The increase of stability increased the heat transfer coefficient of the Al2 O3 nanofluids, making them suitable for heat transfer.